การเสริมเส้นใยอาหารในเฟรนช์ฟรายด์จากมันสำปะหลัง - น้อยด้วง ปิยนุสร์; แก่นแก้ว สุภาสินี (Journal of Food Technology, Siam University, 2015)
จากการศึกษาการผลิตเฟรนช์ฟรายด์จากมันสำปะหลังเสริมเส้นใยอาหารพบว่าเฟรนช์ฟรายด์ที่เสริมเส้นใยอาหารจากเห็ดหูหนูขาวมีลักษณะปรากฏที่ดีกว่าเฟรนช์ฟรายด์ที่เสริมเส้นใยอาหารจากมิวซิเลจ ของเมล็ดแมงลัก และเมื่อทดลองแปรปริมาณเส้นใยเห็ดหูหนูขาวเป็น 3 ระดับ คือ ร้อยละ 1, 2 และ 3 พบว่าเมื่อเสริมเส้นใยอาหารจากเห็ดหูหนูขาวมากขึ้น เฟรนช์ฟรายด์จะมีค่าความแข็งเพิ่มขึ้น โดยมีค่าเท่ากับ 1.95 ± 0.16, 2.50 ± 0.16 และ 3.15 ± 0.20 นิวตัน ตามลาดับ เมื่อนำมาทดสอบคุณสมบัติทางประสาทสัมผัสของเฟรนช์ฟรายด์ที่เสริมเส้นใยอาหารจากเห็ดหูหนูขาว ร้อยละ 1, 2 และ 3 ไม่พบความแตกต่างทางสถิติของคุณลักษณะทุกๆ ด้าน (p > 0.05) แต่พบความแตกต่างในด้านลักษณะปรากฏ โดยเฟรนช์ฟรายด์ที่เสริมเส้นใยอาหารจากเห็ดหูหนูขาว ร้อยละ 3 ได้รับคะแนนการยอมรับลดลงและแตกต่างกันอย่างมีนัยสาคัญทางสถิติ (p 0.05) กับเฟรนช์ฟรายด์ที่เสริมเส้นใยอาหารจากเห็ดหูหนูขาว ร้อยละ 1 และ 2 ผลการวิเคราะห์องค์ประกอบทางเคมี พบว่าเฟรนช์ฟรายด์เสริมเส้นใยอาหารจากเห็ดหูหนูขาว มีปริมาณเส้นใยอาหารสูงสุด คือ ร้อยละ 3.09 ± 0.12 เมื่อเปรียบเทียบกับ เฟรนช์ฟรายด์มันสำปะหลังสูตรมาตรฐานและ เฟรนช์ฟรายด์มันฝรั่งทางการค้า ซึ่งมีค่าร้อยละ 1.27 ± 0.11 และ 0.59 ± 0.03 ตามลำดับ Fiber-Supplemented French Fried Cassava This study was conducted to produce fiber-supplemented French fried cassava. The results showed that the appearance of the French fried cassava supplemented with white jelly fungus (Tremella fuciformis Berk) powder was better than that of the French fried cassava supplemented with the mucilage powder. Then, 3 levels (1, 2 and 3% (w/w)) of white jelly fungus were varied. The results indicated that hardness of French fried cassava increased as substitution levels increased. The hardness of French fried cassava supplemented with white jelly fungus of 1, 2 and 3% (w/w) were 1.95 ± 0.16, 2.50 ± 0.16 and 3.15 ± 0.20 N, respectively. Sensory evaluation of French fried cassava supplemented with 1% 2% and 3% (w/w) of white jelly fungus were not significantly different (p>0.05). The appearance score of French fried cassava supplemented with 3% (w/w) of white jelly fungus was significantly different (p ≤ 0.05) from other formulas. Chemical results showed that French fried cassava supplemented with white jelly fungus has highest fiber content of 3.09 ± 0.12% whereas the fiber content of control and commercial French fried cassava were 1.27 ± 0.11 and 0.59 ± 0.03%, respectively.